Tor Browser Forensics - et. al., Priya P Sajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The TOR Browser is a web browser that anonymizes traffic on the web with the help of Tor network by easily hiding the identity in online platform. It uses onion routing protocol to make use of internet in possible private mode with multiple levels of encryption. These features are being misused for committing many illegal activities such as black market and cyber terrorism. TOR browser takes out all the browsing data and other traces from the network thereby making investigators job a difficult one. This research paper eyes on extracting and analyzing any possible artifacts generated by the TOR browser on local system files and memory dump.